KEPRIBADIAN INTEGRATIF PARA PENDIDIK UNTUK MENINGKATKAN KUALITAS PENDIDIKAN - A. Dirwan (Jurnal Ilmiah Manajemen SURYA PASCA SCIENTIA, 2022)
Abstract : The purpose of this study is to find the necessary basic to be developed in integrated personality of lecture to enhance education quality in Indonesia. The approach used in the study was qualitative approach with grounded theory method. Data was obtained from literature source and respondents were selected by using purposive sampling. Data collection techniques used documentation studies, interviews, and observation. Data analysis used inductive analysis. The results showed that the necessary basic values to be developed in well-integrated personality of lecture to improve education quality in the Indonesian context, those are: first; accepting his own self, second; accepted by other people, third; efficiency in job and study, fourth; free from internal conflict. Keywords : education, quality, personality, lecture.